2015
DOI: 10.4162/nrp.2015.9.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intra-household food distribution and coexistence of dual forms of malnutrition

Abstract: BACKGROUND/OBJECTIVESThe relationship between food intake and nutritional status has been clearly established. Yet, there are only limited studies on food intake among family members and their nutritional status. The study examined the relationship between intra-household food distribution and coexistence of dual forms of malnutrition (DFM) in the same household.SUBJECTS/METHODSHouseholds with a malnourished child and overweight mother were categorized as DFM. Intra-household food distribution among family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
1
17
1
Order By: Relevance
“…Third, even though nutrient consumptions in this study were assessed under the assumption that nutrients are acquired by household members according to energy requirements specific to the individual's age, sex, physical activity level, and so-on, this may not be necessarily the case (e.g. Coates et al 2018;Wibowo et al 2015). This is because intra-household food allocation is determined by relative differences in household members' income, bargaining power, food behaviors, social status, tastes and preferences, and interpersonal relationships (Harris-Fry et al 2017), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Third, even though nutrient consumptions in this study were assessed under the assumption that nutrients are acquired by household members according to energy requirements specific to the individual's age, sex, physical activity level, and so-on, this may not be necessarily the case (e.g. Coates et al 2018;Wibowo et al 2015). This is because intra-household food allocation is determined by relative differences in household members' income, bargaining power, food behaviors, social status, tastes and preferences, and interpersonal relationships (Harris-Fry et al 2017), among others.…”
Section: Discussionmentioning
confidence: 99%
“…The RISKESDAS showed that the prevalence of malnutrition was stable, while the incidence of overweight has increased over the past few years [ 37 38 ]. Judging the nutritional status of adults over 18 years old in Indonesia based on the BMI index in 2013, 11.09% of the population were underweight while 11.48% were overweight and 14.76% obesity; this indicates an increasing problem of obesity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the classification of undernourished children differs between studies in terms of the indicators used and the cut-off points applied [8]. Indicators of child undernutrition used in existing DB research are weight-for-age Z-scores (WAZ) [13, 16], height-for-age Z-scores (HAZ) [14, 17–20], BMI-for-age Z-score (BAZ) [6], simple BMI [5], or combinations of WAZ, HAZ and weight-for-height Z-scores (WHZ) [21, 22]. Given these differences in measurement, comparability of studies is difficult.…”
Section: Introductionmentioning
confidence: 99%